2017
DOI: 10.1073/pnas.1620562114
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of point-mutated KRAS through artificial microRNAs

Abstract: Mutated protein-coding genes drive the molecular pathogenesis of many diseases, including cancer. Specifically, mutated KRAS is a documented driver for malignant transformation, occurring early during the pathogenesis of cancers such as lung and pancreatic adenocarcinomas. Therapeutically, the indiscriminate targeting of wild-type and point-mutated transcripts represents an important limitation. Here, we leveraged on the design of miRNA-like artificial molecules (amiRNAs) to specifically target point-mutated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Finally, a major unmet issue in melanoma is targeting mutated forms of NRAS kinases, which are still considered undruggable. Thus, alternative strategies including siRNAs and artificial-miRNAs (amiRs) have been proposed for directly inhibiting the downstream transduction of specific RAS point-mutations [112,113]. Innovative nano-carriers are currently under investigation as a possible system for the selective delivery of these molecules into cancer cells [114,115].…”
Section: Clinical Applications Of Extracellular Vesicles and Melanomamentioning
confidence: 99%
“…Finally, a major unmet issue in melanoma is targeting mutated forms of NRAS kinases, which are still considered undruggable. Thus, alternative strategies including siRNAs and artificial-miRNAs (amiRs) have been proposed for directly inhibiting the downstream transduction of specific RAS point-mutations [112,113]. Innovative nano-carriers are currently under investigation as a possible system for the selective delivery of these molecules into cancer cells [114,115].…”
Section: Clinical Applications Of Extracellular Vesicles and Melanomamentioning
confidence: 99%
“…through computational analysis, artificially generated miRNAs can be engineered that selectively target genes with single nucleotide mutations that contribute to the tumorigenic phenotype without affecting the wild-type gene. 168 this method can be expanded to designing miRNAs that selectively target genes only involved in pathology of the disease while eliminating targeting of irrelevant genes, thus preventing side-effects associated with unwanted targeting. An algorithm that may be useful for predicting such designer miRNAs is miRBooking.…”
Section: Resultsmentioning
confidence: 99%
“…Point mutations in miRNA target genes can be harnessed to develop powerful, targeted cancer therapies. Acunzo et al [60] devised miRNA-like artificial molecules (amiRNAs) and showed that amiR-KS3 specifically targets mutant KRAS transcripts carrying the G12S mutation without affecting wild-type transcripts in NSCLC. This amiR-KS3 treatment was also found to be effective in other cancers associated with G12S mutation.…”
Section: Genetic Mutations Can Alter Post-transcriptional Regulationmentioning
confidence: 99%